Multispecies tracking reveals a major seabird hotspot in the North Atlantic. Issue 5 (2nd August 2021) - Davies, Tammy E.; Carneiro, Ana P.B.; Tarzia, Marguerite; Wakefield, Ewan; Hennicke, Janos C.; Frederiksen, Morten; Hansen, Erpur Snær; Campos, Bruna; Hazin, Carolina; Lascelles, Ben; Anker‐Nilssen, Tycho; Arnardóttir, Hólmfríður; et al.
Abstract: The conservation of migratory marine species, including pelagic seabirds, is challenging because their movements span vast distances frequently beyond national jurisdictions. Here, we aim to identify important aggregations of seabirds in the North Atlantic to inform ongoing regional conservation efforts. Using tracking, phenology, and population data, we mapped the abundance and diversity of 21 seabird species. This revealed a major hotspot associated with a discrete area of the subpolar frontal zone, used annually by 2.9–5 million seabirds from ≥56 colonies in the Atlantic: the first time this magnitude of seabird concentrations has been documented in the high seas. The hotspot is temporally stable and amenable to site‐based conservation and is under consideration as a marine protected area by the OSPAR Commission. Protection could help mitigate current and future threats facing species in the area. Overall, our approach provides an exemplar data‐driven pathway for future conservation efforts on the high seas.